Retail Pharmacies and Drug Diversion during the Opioid Epidemic - Aljoscha Janssen; Xuan Zhang (Research Institute of Industrial Economics (IFN), 2020)
This study investigates the role of retail pharmacy ownership in the opioid epidemic in the United States by comparing independently owned pharmacies' and chain pharmacies' prescription opioid dispensing practices. Using data of prescription opioid orders at the pharmacy level between 2006 and 2012, we find that compared to chain pharmacies within the same ZIP code area, independent pharmacies on average dispense 40.9% more opioids and 61.7% more OxyContin. We further confirm that after being acquired by a chain, a previously independent pharmacy reduces dispensing of opioids by 31.7% and OxyContin by 43%. Using the Oxy-Contin reformulation in 2010, which reduced the demand for diversion for illegal recreational use but not the demand for medical use, we show that half of the difference in dispensed Oxy-Contin doses between independent and chain pharmacies can be attributed to drug diversion. In addition, we find that independent pharmacies' OxyContin dispensing is higher in areas with greater competition. Furthermore, a larger county-level recreational demand is correlated with a larger difference between independent and chain pharmacies' prescription opioid dispensing. We discuss two reasons that may explain why independent pharmacies are more likely to be linked to drug diversion. First, they have stronger financial incentives due to lower expected costs of misdoing. Second, they may have less information on patients' prescription drug use history. Prescription drug monitoring programs help to reduce the information gap between independent and chain pharmacies to some extent, but monitoring of small independent pharmacies needs to be strengthened.
Keywords: I11; I18; L22; 330; Pharmacy; Ownership; Prescription opioids; Drug diversion